2013
DOI: 10.3109/1354750x.2013.787460
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma neutrophil gelatinase-associated lipocalin (NGAL) with sepsis and acute kidney dysfunction

Abstract: Plasma NGAL can help clinicians to identify bacterial infections in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 36 publications
3
34
0
1
Order By: Relevance
“…The fact that NGAL levels are correlated with CPB time and that homodimeric NGAL is the predominant form in these patients' urine [53] suggests that the neutrophils, rather than the kidney tubular cells, are the main source. Similar conclusions can be drawn from general ICU populations where sepsis is associated with elevated plasma NGAL independent of degree of renal impairment [37,54]. …”
Section: Ngal In Acute Kidney Injurysupporting
confidence: 56%
“…The fact that NGAL levels are correlated with CPB time and that homodimeric NGAL is the predominant form in these patients' urine [53] suggests that the neutrophils, rather than the kidney tubular cells, are the main source. Similar conclusions can be drawn from general ICU populations where sepsis is associated with elevated plasma NGAL independent of degree of renal impairment [37,54]. …”
Section: Ngal In Acute Kidney Injurysupporting
confidence: 56%
“…Another issue is that NGAL production is increased by complex inflammatory responses and organ damage that occurs in sepsis (14,28,29). Although the high levels of sNGAL could be a result of its production from neutrophils and other injured organs in sepsis, sNGAL levels were not different between the BiNx/BUO alone and BiNx/BUO with CLP groups (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Martensson et al (25) found that elevated plasma NGAL, procalcitonin, and CRP are associated with sepsis independent of the level of kidney function and that NGAL outperforms procalcitonin and CRP as a marker to distinguish bacterial infection from noninfective causes of systemic inflammatory response syndrome by analysis of more than 1,300 plasma samples. In our study, the relationship between increased NGAL and AKI is evident in which high NGAL is strongly associated with increased creatinine, reduced eGFR, and more frequent hypoperfusion and thus likely AKI.…”
Section: Discussionmentioning
confidence: 98%